A - Abbey, Robert (Oxford University Press, 2003)
Now in its second edition, this successful text offers practical advice and solutions in the complex area of commercial conveyancing and property. It provides detailed explanations of the structure and content of the modern business lease including rent review, lease covenants, and service charges, and includes a point-by-point study of the termination and renewal procedures with reference to the relevant legislative covenants